Selection of pre-school teacher by using multi-criteria decision making methods - Syarifah Nur Aisyah Syed Mohd. Amin, 1992-, author; Rashidah Ahmad, 1960- , supervisor; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains) - Universiti Teknologi Malaysia, 2017